Back-to-School Upper Respiratory Infection in Preschool and Primary School-Age Children in Israel. Issue 5 (May 2015) - Perry Markovich, Michal; Glatman-Freedman, Aharona; Bromberg, Michal; Augarten, Arie; Sefty, Hanna; Kaufman, Zalman; Sherbany, Hilda; Regev, Liora; Chodick, Gabriel; Mendelson, Ella; Shohat, Tamy; Mandelboim, Michal
<x xml:space="preserve">Abstract</x> Background: Increased upper respiratory infection (URI) among children at the beginning of school year is well known to parents and pediatricians. However, this phenomenon is not well documented or characterized. Methods: Computerized datasets from a large health maintenance organization in Israel were used to calculate the weekly rates of URI among children 3–14 years old for the years 2007–2012. In addition, nasopharyngeal swabs were collected in 2010–2012 from children with URI symptoms and controls during school opening time. Swabs were tested by real-time polymerase chain reaction for the presence of respiratory viruses. Results: Time-series analysis demonstrated a peak of URI in September each year. The peaks reached their height 2 weeks after school opening and returned to baseline within 4–7 weeks. The main 3 viruses detected both in URI patients and in healthy controls during the first weeks of school opening were rhinovirus, adenovirus and enterovirus. The detection rate of any respiratory virus, and of rhinovirus in particular, was significantly higher among cases than among controls (54% vs. 16%, P < 0.001 for any virus, and 35% vs. 6.0%, P < 0.01 for rhinovirus). When adjusting for age and sex cases had 5.8 times more viral detection when compared with controls. Upper respiratory symptoms were significantly more prevalent among the virus-positive cases when compared with negative ones. Conclusions: Back-to-school illness consisting of URI has a distinct epidemiological pattern demonstrating a rapid rise peaking within 2 weeks of school opening and is associated predominantly with rhinovirus.